Predictors of perceived barriers to physical activity in the general adult population: a cross-sectional study (2017)
Background: The perception of personal barriers to physical activity varies according to the sociodemographic characteristics of individuals. Objective: To determine the predictors of the perception of barriers to physical activity in the adult population. Method: A cross-sectional study with 1066 adult women and 1036 adult men. The sociodemographic variables (age, gender, marital status, socioeconomic level, level of education), the perception of barriers that do not allow performance of physical activity (i.e. lack of time, social support, energy, motivation, skill, resources, and fear of injury during practice); and the level of physical activity through the International Physical Activity Questionnaire in its short-form version were evaluated. Results: Individuals from low socioeconomic level (1 and 2) have higher risks of perceiving barriers such as lack of motivation [OR 1.76 (95% CI (1.4---2.1))] and lack of resources [OR 1.37 (95% CI (1.1---1.6))]; individuals with partners did not perceive the lack of social support [OR 0.29 (95% CI (0.2---0.4))] and lack of motivation [OR 0.54 (95% CI (0.4---0.7))] as barriers to physical activity. Individuals with low schooling perceived lack of social support [OR 3.81 (95% CI (3---4.7))], lack of resources [OR 2.78 (95% CI (2.2---3.3))], and fear of injury [OR 2.70 (95% CI (2.2---3.3))] as barrier to physical activity. Conclusion: Factors such as socioeconomic level, marital status, level of education, and selfperception of health are predictors of barriers to physical activity.